Pengaruh Budaya Organisasi, Religiusitas Dan Whistleblowing System Terhadap Pencegahan Fraud Dalam Pengelolaan Keuangan Desa Se- Kecamatan Denpasar Utara - Anak Agung Ayu Puja Mas Sukasih; Ni Komang Sumadi; Ni Putu Fery Karyada (Hita Akuntansi dan Keuangan, 2025)
The huge proportion of Town Funds administered by the Central Government to Town State run organizations doesn't block the opportunity of coercion or control in their organization. Distortion or cheating according to the Indonesian Groundwork of Public Clerks is a conscious exhibition by something like one individuals in organization or social events obligated for organization, delegates and outcasts which incorporates the usage of confusion to secure a nonsensical advantage or negligence the law ( IAPI - Indonesian Foundation of Public Clerks). The general population in this study was all town specialists amounting to 216 people from 8 towns in North Denpasar District. The amount of tests in this survey was 64 people who were settled using a purposive looking at strategy and had a go at using different direct backslide assessment techniques. The outcomes of this investigation show that various leveled culture fundamentally influences distortion aversion. Legalism influences hindering deception. The whistleblowing structure influences hindering blackmail